PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI (STUDI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2023) - Aprilio Artanto; Yona Octiani Lestari (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Corporate Social Responsibility (CSR) is defined as a company's commitment that involves sustainable practices and socio-environmental concerns, which not only reduce negative impacts but also improve the image and good relations with stakeholders. This study aims to analyze the influence  of corporate social responsibility on company value with profitability as a moderation variable in mining companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative descriptive method using secondary data obtained through the official website of the Indonesia Stock Exchange (IDX), namely www.idx.co.id The sample of this study includes a total of 83 mining companies and 13 companies that meet the criteria for the period 2019-2023. The analysis method applied in this study was a moderation regression (MRA) analysis model. Profitability is used as a moderation variable to see if profits can strengthen or weaken the relationship between independent variables and the value of a company in a mining company. The results of hypothesis testing from this study prove that Corporate Social Responsibility and profitability show no significant influence on the company's value. Profitability is also not able to moderate the relationship between CSR and company values.